Regarding Scientific Discussion on Legal Nature of the Law Abuse (Law and Safety, 2021)
The authors have analyzed the facts inherent in the equitable right that can lead to abuse of law. It has been emphasized that the legal literature has no single approach to the definition of the term of “law abuse”. However, there is a number of factors that influence the existence of such a specific phenomenon as “law abuse”.Attention has been paid to the species classification of law abuse. It has been noted that depending on what public relations are harmed in the process of exercising the right contrary to its purpose, law abuse can be divided into lawful (legal) and illegal. The general characteristic of lawful (legal) and illegal abuse of law has been presented; their features have been named. It has been emphasized that abuse of law can also be classified by the branch (abuse of property rights, abuse of rights in criminal law, white collar crime within public administration sphere). Attention has been paid to the fact that each of the forms of law abuse can be divided into types and subspecies depending on the means of abuse, i.e. depending on the type of equitable right or jurisdiction as elements of legal capacity, which are abused.As a result, it has been concluded that the peculiarities of modern legislation, in particular the presence of conflicting rules, gaps and contradictions, can lead to abuse of law. This is mainly the case when the equitable right corresponds to an obligation for non-fulfillment of which there is no legal liability at the level of legislation.As a result, it has been noted that law abuse can be currently classified on various grounds, but it should be understood that any classification will reflect only part of the features of the studied phenomenon.
Keywords: law; law norm; legally significant behavior; qualification; equitable right; abuse; law abuse